Thyroid Autoimmunity and Thyroid Cancer – The Pathogenic Connection: A 2018 Update - Nagayama, Yuji (Hormone and Metabolic Research, 2018)
The association between thyroid cancer and thyroid autoimmunity has long been suggested, but remains to be elucidated for several decades. Here the data on this issue are updated by summarizing relevant papers published between 2012 and early 2018. Although numerous papers demonstrated the significant increase in the prevalence of thyroid autoimmunity (positive intrathyroidal lymphocyte infiltration and/or anti-thyroglobulin/thyroid peroxidase antibodies) in patients with thyroid cancers as compared to those with benign nodules, and also the significant increase in the prevalence of papillary thyroid cancer (PTC) in patients with thyroid autoimmunity as compared to those without, there are some crucial biases that should be taken into account for their interpretation. However, a difference in the incidence of thyroid autoimmunity in patients with PTCs and those with other types of thyroid cancers appears to support the significant association of two conditions. Thyroid autoimmunity is, at least partly, likely to be elicited against antigens shared by normal and cancerous thyroid tissues, thereby inducing autoimmunity. At the same time, elevated TSH levels (even within the normal reference ranges), which often accompany Hashimoto’s patients are a risk factor for thyroid cancer. However, it is still unclear whether or not the co-existence of thyroid autoimmunity impacts on cancer characteristics and prognosis. This issue needs to be further investigated with large-scale prospective studies.
Keywords: papillary thyroid cancer; TSH; benign nodule; bias